ANALISIS KONDISI SOSIAL EKONOMI PETANI KERAMBA DI KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Gusman Jeni; Wali Aya Rumbia; Ahmad Ahmad (Universitas Halu Oleo, 2021)
This study aims to determine how the Socio-Economic Conditions of Keramba Farmers in Kulisusu District of North Buton Regency, using quantitative descriptive methods. The sample in this study was as many as 13 cage farmers. The analytical tool used is Revenue Analysis. The results showed that there were 6 cage farmers or 46.15% elementary school education level, 2 people or 15.39% junior high school education level, and 5 people or 38.46% high school education level. The educational condition of cage farmers is still considered low. In terms of health conditions, judging by the place of treatment is considered sufficient; there were 8 people or 61.54% went to the hospital and 5 people or 38.46% went to the health center for reasons of good service and practical treatment. Whereas in terms of the economic condition of net cage farmers, the net income received is Rp 244,814,000 / harvest season with an average of Rp 18,831,846 / harvest season categorized as high.